Antimicrobial Activity of Acacia nilotica - Elizabeth, K.M.; Sireesha, D.; Nageswara Rao, K.; Basaveswara Rao, M.V. (Asian Journal of Chemistry, 2010)
The antimicrobial activity of Acacia nilotica was tested by disc diffusion method against a panel of human pathogenic microorganisms. The chloroform extract of A. nilotica stem bark, at a concentration of 400 μg/disc showed the zones of inhibition ranging from 13 to 24 mm against 1x107 microbial cells with largest zone against S. aureus indicating that this herbal extract was strongly inhibitory towards this microorganism and least to A. niger. The minimal inhibitory concentrations (MICs) were determined by broth dilution technique which ranged between 200-1600 μg/mL, S. aureus with lowest MIC value and P. aeruginosa and A. niger with highest MICs indicating that S. aureus was strongly inhibited and P. aeruginosa, A. niger, the least. The biochemical alterations induced by this plant extract were assessed by performing several biochemical tests. There was inhibition of protease and amylase activities of these microorganisms following treatment with the extract. These results indicate that A. nilotica possesses potent broad spectrum antimicrobial activity against all microorganisms tested.